ISOLASI DAN KARAKTERISASI SENYAWA ALKALOID DARI DAUN ALPUKAT (PERSEA AMERICANA MILL) - Tengo, Nilda Apriyati; Bialangi, Nurhayati; Suleman, Nita (Sainstek, 2013)
The aims of this study is to isolate and find the alkaloid compounds contained in the leaves of avocado (Persea americana Mill). The method used is the isolation of pure compounds to obtain isolates. 400 g of avocado leaves macerated with methanol solvent yield 53.41 gr of methanol extract. The results of column chromatography I yield 17 fractions, the fraction N12 is re-elected for column chromatography II. The results of chromatography N12 obtained isolate pure in fractions 7. This isolate is tested purity by using thin layer chromatography with eluent variations produce a single stain pattern, so it can proceed with the test isolate phytochemicals. The results of IR spectrophotometer data interpretation, isolate pure fractions 7 indicates the presence of alkaloid compounds having functional groups N-H (3311.55 cm-1), C-H aliphatic (2921.96 cm-1, 2850.59 cm-1), C=O (1735.81 cm-1, 1641.31 cm-1), C-N (1240.14 cm-1, 1130.21 cm-1), C-H Aromatic (910.34 cm-1, 846 cm-1), N-C=O (580.53 cm-1). The results of UV-Vis spectrophotometer from fractions 7 gives absorption wavelength of 238.5 nm indicating the occurrence of electron transition n * and n * which indicates the existence of C=O and N-H groups.